Compras públicas sustentáveis: proposta metodológica e análise dos critérios socioambientais utilizados em editais de licitações de dois campi da Universidade de São Paulo - Pereira, Gisele Sant’ana Fiorini (2019)
Debates on the concept of sustainable public procurement have gained more space in public management guidelines, even though most public administration still do not know or do not use these practices. The objective of this work was to verify if the socio-environmental standards of sustainable public procurement according to the Brazilian legislations are being incorporated in governmental biddings. Therefore, a bibliographical review was done on sustainable public procurement in Brazil. The main legislation aimed at regulating the use of this practice was identified, founding the benefits of its use and the obstacles faced by the public administration for its implantation. A methodology was proposed for the identification of socio-environmental standards in public procurement for the sustainable purchase of microcomputers, based on the evaluation of the product life cycle and the pertinent legislation. After the identification of the standards, an analysis was made of how these can be evidenced in an objective manner in the bidding documents. As a result of this methodological proposal, the Matrix of Identification of the Socio-Environmental Standards for the Acquisition of Microcomputers was made. Subsequently, a case study was made to analyze the use of social and environmental standards in bidding documents for the acquisition of microcomputers from two campuses of the University of São Paulo. The growing number of legislations on sustainable public procurement over the years shows the importance of the issue to public agencies. The methodology proposed for the identification of socio-environmental standards in public procurement was effective and could be extended to the acquisition of other goods, provided that it is adapted according to the analysis of the product life cycle and the legislation pertinent to the goods or service that will be purchased. The developed case study showed a low incorporation of socio-environmental standards in USP's bidding documents, but an efficient way of guaranteeing compliance with the legislation relevant to sustainable public procurement is the incorporation of these standards into the fixed information of public notice pre-approved by the university. The request for environmental certifications proved to be an important tool to demonstrate the fulfillment of the socio-environmental standards in the acquisition of microcomputers. Given these results, it is concluded that, in general, there is a significant amount of legislation that requires and supports the use of sustainability standards in public procurement, but these are ignored by the public administration, both by the executing agency of the bidding, and by the oversight body of public accounts. It is hoped that sustainable public procurement will be the rule and not the exception in the near future, where the public administration must act as a protagonist, incorporating standards and good practices of sustainability in its activities and in its bidding documents for goods and services, contributing to changes in society's production and consumption patterns for sustainable development.